Distortion Type Theorems for Functions in the Logarithmic Bloch Space. (16th April 2017) - García-Ortíz, Armando J.; Lesmes Acosta, Milton del Castillo; Ramos-Fernández, Julio C.
Abstract : We establish distortion type theorems for locally schlicht functions and for functions having branch points satisfying a normalized Bloch condition in the closed unit ball of the logarithmic Bloch space B l o g . As a consequence of our results we have estimations of the schlicht radius for functions in these classes.